Effect of blend ratio on aging, oil and ozone resistance of silica-filled chloroprene rubber/natural rubber (CR/NR) blends (eXPRESS Polymer Letters)
The effect of blend ratio on properties of chloroprene rubber/natural rubber (CR/NR) blends was investigated. In addition to the mechanical properties, attention was also given to the resistance to thermal aging, oil and ozone of the blends. Silica was selected as a reinforcing filler in this study due to its unique characteristic to interact with CR. The results reveal that, due to the better filler dispersion and the greater crosslink density, the silica-filled CR possesses lower compound viscosity and better mechanical properties, compared to the silica-filled NR. The aging properties, oil and ozone resistance of the silica-filled CR are also significantly better than those of the silica-filled NR. The mechanical properties and the resistance to degradation of the silica-filled CR/NR blends are mainly governed by the blend morphology. It is found that good mechanical properties in association with adequately high resistance to degradation from thermal aging and oil are obtained when CR remains the matrix in the blends. Even though the ozone cracks are found in all blends, a thorough look at the results reveals that considerable improvement in ozone resistance is achieved with increasing CR content.